2019
DOI: 10.1007/s11199-018-0985-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Men’s Feminization and Attitudes Toward Homosexuality: Heterosexual Men’s Reactions to the Decline of the Anti-Femininity Norm of Masculinity

Abstract: One of the central dimensions of traditional masculinity is men's renunciation of the feminine (i.e., the anti-femininity norm), and men's endorsement of this norm constitutes one of the strongest predictors of negative attitudes toward homosexuality. However, egalitarian societies are undergoing a significant change: Gendered roles, stereotypes, and norms are evolving. Accordingly, many believe that men are becoming more feminine than before, and this change might have consequential effects. Across two studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 76 publications
6
51
1
1
Order By: Relevance
“…Indeed, the straight defaulting, and not the inferred homosexual sexual orientation, appeared to be especially sensitive to category information concerning the racial group. Consistent with studies showing that the perceivers' attribution of a heterosexual sexual orientation to a given target is embedded with the perceived lack of femininity in that target (Falomir-Pichastor et al, 2019), we found that Asian men were stereotyped as more feminine than Black men, and this stereotyping covaried with the lower probability that Asian men were thought to be heterosexual men compared to Black men, and not with a higher probability that Asian men were thought to be gay men compared to Black men (Study 3). In other words, the stronger presence of the gender nonconformity characteristic in the representation of Asian men was associated with an Extrapolating sexual orientation from race categories 35 attenuation of the ESOS of this group as heterosexual but not with an enhancement of the ESOS of this group as gay.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, the straight defaulting, and not the inferred homosexual sexual orientation, appeared to be especially sensitive to category information concerning the racial group. Consistent with studies showing that the perceivers' attribution of a heterosexual sexual orientation to a given target is embedded with the perceived lack of femininity in that target (Falomir-Pichastor et al, 2019), we found that Asian men were stereotyped as more feminine than Black men, and this stereotyping covaried with the lower probability that Asian men were thought to be heterosexual men compared to Black men, and not with a higher probability that Asian men were thought to be gay men compared to Black men (Study 3). In other words, the stronger presence of the gender nonconformity characteristic in the representation of Asian men was associated with an Extrapolating sexual orientation from race categories 35 attenuation of the ESOS of this group as heterosexual but not with an enhancement of the ESOS of this group as gay.…”
Section: Discussionsupporting
confidence: 80%
“…Existing research has indeed shown that perceived men's feminization increases heterosexual men's endorsement of the heterosexuality norm; that is, they distance themselves psychologically from gay men and express more negative attitudes towards homosexuality (Falomir-Pichastor et al, 2019). Furthermore, this tendency is accounted for by heterosexual men's motivation to increase in-group distinctiveness (i.e., to psychologically exclude gay men from the male in-group; Iacoviello et al, 2019) and is greater among participants who strongly endorse traditional masculinity norms (Falomir-Pichastor et al, 2019;Valsecchi et al, 2020).…”
Section: The Role Of Perceived Men's Feminizationmentioning
confidence: 99%
“…In the end, 173 participants completed the online questionnaire. Because heterosexuality is one of the most relevant dimension of masculinity (e.g., Bosson et al, 2006;Falomir-Pichastor et al, 2019;Herek, 1986), and because gay men (as compared with heterosexual men) are likely to interpret and react very differently to items regarding the 'negativity toward sexual minorities' and 'disdain for homosexuals' dimensions of traditional masculinity, the present research focuses on heterosexual male participants. Consequently, we excluded participants who said they were not heterosexual (n = 10).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, future studies should examine whether this disparity exists in the case of traditional masculinity norms and, if it does, why? More research is also needed to provide a better understanding of men's reactions to changes in masculinity norms, both in society as a whole and among men (Falomir-Pichastor et al, 2019;Iacoviello et al, 2020).…”
Section: Is Traditional Masculinity Still Valued?mentioning
confidence: 99%